The synthesis of 3-amino-5-arylisothiazoles from propynenitriles. Issue 9 (28th February 2018) - Barton, Peter
Graphical abstract: Highlights: Novel synthesis of 3-amino-5-arylisothiazoles. Tolerant to a range of functional groups. Operationally simple. Abstract: A new synthesis of 3-amino-5-arylisothiazoles is reported. The reaction is operationally simple, utilises readily synthesised propynenitriles as starting materials and is tolerant of a range of functional groups. The optimised reaction conditions can also be used with 3-chloropropenenitriles in place of propynenitriles.